Language Perceptions and Their Impact on Second Language Acquisition: A Sri Lankan Perspective - Dayananda, GMCM; Marikar, Faiz Mmt (Nepalese Linguistics, 2025)
Second language acquisition in Sri Lanka is deeply influenced by learners’ and teachers’ perceptions, which shape classroom interaction, motivation, and overall performance. Despite the centrality of English in higher education and employment, many students encounter barriers rooted not only in language competence but also in their attitudes and beliefs about learning. This study examines how such perceptions affect the teaching–learning process, arguing that psychological and socio-cultural dimensions are as important as pedagogical strategies. By exploring both the student and lecturer perspectives, the research highlights the need to prioritize belief systems and attitudes in curriculum design and classroom practice. Addressing these factors is essential for fostering more effective and sustainable second language acquisition, thereby contributing to educational improvement and broader social mobility in the Sri Lankan context.